2021
DOI: 10.1093/molbev/msab281
|View full text |Cite
|
Sign up to set email alerts
|

Visual Gene Expression Reveals a cone-to-rod Developmental Progression in Deep-Sea Fishes

Abstract: Vertebrates use cone cells in the retina for colour vision and rod cells to see in dim light. Many deep-sea fishes have adapted to their environment to have only rod cells in the retina, while both rod and cone genes are still preserved in their genomes. As deep-sea fish larvae start their lives in the shallow, and only later submerge to the depth, they have to cope with diverse environmental conditions during ontogeny. Using a comparative transcriptomic approach in 20 deep-sea fish species from eight teleost … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(58 citation statements)
references
References 60 publications
5
53
0
Order By: Relevance
“…cone SWS1, SWS2, RH2, LWS and rod RH1 ), and detected a clear increase of GNAT1 : GNAT2 ratio with ageing, with the exception of the Aulopiformes deep-sea fishes. In this group, a rare discordance between the dominating opsin type (rod-specific) and phototransduction cascade genes (cone-specific) in adults suggests a presence of possibly transmuted photoreceptors, and an overall intriguing visual system which needs to be investigated further (Fig 3, Lupše et al 2021).…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…cone SWS1, SWS2, RH2, LWS and rod RH1 ), and detected a clear increase of GNAT1 : GNAT2 ratio with ageing, with the exception of the Aulopiformes deep-sea fishes. In this group, a rare discordance between the dominating opsin type (rod-specific) and phototransduction cascade genes (cone-specific) in adults suggests a presence of possibly transmuted photoreceptors, and an overall intriguing visual system which needs to be investigated further (Fig 3, Lupše et al 2021).…”
Section: Resultsmentioning
confidence: 95%
“…Functionally, rods generally allow for an improvement in visual acuity and startle responses in fishes (Fuiman 1993, Pankhurst et al 1993, Fuiman and Delbos 1998) and are also associated with motion sensitivity and the appearance of novel behaviours, such as schooling (Hunter & Coyne 1982). More specifically, higher rod expression increases individual performance of fishes living in the deep-sea (de Busserolles et al 2020, Lupše et al 2021). Additionally, laboratory experiments have shown that the ability to follow a rotating stripe pattern (the optomotor drum) might be dependent on rod formation and retinal development, as it is not seen in stages or specimens lacking rods (Blaxter 1986, Carvalho et al 2002, Magnuson et al 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Contrastingly, in fishes which adopt dim environments, visual development seems to be characterised by a more rapid and extreme version of these changes. For example, some deep-sea fishes seem to possess cones as larvae but progress to having only rods in adulthood (Bozzano et al 2007;de Busserolles et al 2014a;Lupše et al 2021). However, most of the previous studies on visual development in dim environments focused on deep-sea fishes (Cortesi et al 2020).…”
Section: Introductionmentioning
confidence: 99%